Pengendalian Kualitas di Line Painting Menggunakan Metode Six Sigma: Studi Kasus di PT ABC - Telma Anis Safitri; Laily, Salsa Afni; Muhammad, Katon (Valid: Jurnal Ilmiah, 2024)
PT ABC is a company engaged in bicycle manufacturing. In its production process, PT ABC places great emphasis on product quality. Based on company defect data from October to December 2023, defects in line painting were consistently observed in every production run. This study aims to identify the predominant defects, determine the company's sigma level, ascertain the root causes of these predominant defects, and propose corrective actions. This research employs the Six Sigma methodology, using the Defects Per Million Opportunities (DPMO) calculation to determine the sigma level, and the DMAI (Define, Measure, Analyze, Improve) approach to identify root causes and recommend improvements. The results indicate that the company operates at a sigma level of 3, with the predominant defect being "dust spray." The root causes of the dust spray defect include human factors such as lack of attention to detail and insufficient operator skills, material factors such as the incorrect viscosity of the clear coat used, method factors including the absence of an official Standard Operating Procedure (SOP) from the company, and machine factors such as unscheduled machine maintenance.